2009
DOI: 10.1097/tp.0b013e3181a36e5e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Toll-Like Receptor 4 (TLR4)-Mediated Inflammation After Cold Ischemia/Reperfusion in the Heart

Abstract: Background TLR4 signaling mediates early inflammation after cold I/R. We hypothesized that the TLR4 co-receptor CD14, the intracellular adaptor proteins MyD88 and TRIF would be required for cold I/R induced inflammation. HMGB1 is a putative endogenous activator of TLR4. Therefore, we also assessed the contribution of HMGB1 in cold I/R induced inflammation. Methods Syngeneic heart transplants were performed in mice deficient in CD14, MyD88, TRIF, or wild-type mice. In other experiments, anti-HMGB1 neutralizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 59 publications
(53 reference statements)
0
84
0
Order By: Relevance
“…TLRs play critical roles in many disease conditions, including the pathogenesis of atherosclerosis (25, 26), chronic cardiac allograft rejection (27), liver and heart ischemia/reperfusion injury (28)(29)(30), and type 1 diabetes (31)(32)(33). Several groups have demonstrated that TLR4 activation is directly involved in the chronic rejection of transplanted organs (27,34).…”
Section: Discussionmentioning
confidence: 99%
“…TLRs play critical roles in many disease conditions, including the pathogenesis of atherosclerosis (25, 26), chronic cardiac allograft rejection (27), liver and heart ischemia/reperfusion injury (28)(29)(30), and type 1 diabetes (31)(32)(33). Several groups have demonstrated that TLR4 activation is directly involved in the chronic rejection of transplanted organs (27,34).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4-deficient mice are also protected during hepatic ischemia-reperfusion injury. Compelling evidence using TLR4-defective mice also supports a role for a HMGB1-TLR4 axis in hemorrhagic shock/resuscitation-induced injury, systemic inflammation, and end-organ damage induced by bilateral femur fractures (81,82).…”
Section: Hmgb1 Trauma and Sterile Inflammationmentioning
confidence: 99%
“…Our results indicate that factor B synthesis and release is highly dependent on MyD88, but independent of TLR9. We have previously demonstrated that myocardial injury after cold I/R is also largely dependent on MyD88 (50). RNA polymerase III has also been shown to detect DNA in the cytosol and trigger activation of the immune system through RIG-I (51,52).…”
Section: Discussionmentioning
confidence: 99%